2016
DOI: 10.3892/ol.2016.4801
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Rab27B is correlated with distant metastasis and poor prognosis in ovarian cancer

Abstract: Abstract. The secretory small guanosine-5'-triphosphate-binding enzyme, Rab27B, has been identified to be an oncogene that is involved in the progression of certain tumors. The current study was designed to evaluate the expression pattern of Rab27B in ovarian cancer (OC), borderline tumors and benign ovarian adenoid tumors, as well as its association with survival prognosis and clinical parameters. The expression of Rab27B protein was examined by immunohistochemistry in 204 patients who had undergone ovarian r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
4
20
0
Order By: Relevance
“…YU JIANG 1* , XIAOHUI WANG 2* , JI ZHANG 3 (13). Deregulation of RAB27B has been observed in a number of common cancer types (14,15). For instance, RAB27B was determined to be significantly upregulated in ovarian cancer tissues, where it was associated with distant metastasis and poor prognosis (15).…”
Section: Microrna-599 Suppresses Glioma Progression By Targeting Rab27bmentioning
confidence: 99%
“…YU JIANG 1* , XIAOHUI WANG 2* , JI ZHANG 3 (13). Deregulation of RAB27B has been observed in a number of common cancer types (14,15). For instance, RAB27B was determined to be significantly upregulated in ovarian cancer tissues, where it was associated with distant metastasis and poor prognosis (15).…”
Section: Microrna-599 Suppresses Glioma Progression By Targeting Rab27bmentioning
confidence: 99%
“…Previous studies have found that high Rab27B expression is related to prognosis in patients with hepatocellular carcinoma, pancreatic ductal ADC, ovarian cancer, and gastrointestinal tumors; our findings are consistent with these results. 6,7,9,18 In addition, other studies have shown that Rab27A has a prognostic effect in several cancers, including hepatocellular carcinoma, colorectal cancer, glioma, and pancreatic ductal ADC. 7,13,14,16,19 However, we did not observe any relationship between Rab27A expression and prognosis in patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…reported that Rab27A controls exosome secretion in lung adenocarcinoma (ADC) cells . Furthermore, some reports have demonstrated that Rab27A and Rab27B are associated with tumor progression and have been used as a prognostic factor in hepatocellular carcinoma; glioma; and pancreatic, ovarian, and colorectal cancers …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations